2008
DOI: 10.1007/s12253-008-9015-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photon with Electron Boost in Treatment of Early Stage Breast Cancer

Abstract: In the treatment of early stage breast cancer breast conserving surgery (BCS) followed by whole breast irradiation (WBI) is a standard method. The impact of the tumor bed boost following WBI is well-defined, but there are various delivery methods. In this study the electron and the photon boost techniques were compared. For 78 early stage breast cancer patients both CT based 3D conformal photon boost and electron boost plans were created. For dosimetric comparison coverage index (CI), external volume index (EI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Good and excellent cosmetic scores were observed in 80% patients of both arms at the end of 2 years. Similar results were observed by Kovacs et al, in the above study, [28] in which they reported good and excellent cosmetic scores in 88.3% and fair cosmetic score in 11.6% of 3DCRT photon boost patients at the end of 4 years follow-up. Thus, indicating the fact that breast cosmesis improves with time, post-radiation, and better appreciated in long-term follow up studies.…”
Section: Discussionsupporting
confidence: 91%
“…Good and excellent cosmetic scores were observed in 80% patients of both arms at the end of 2 years. Similar results were observed by Kovacs et al, in the above study, [28] in which they reported good and excellent cosmetic scores in 88.3% and fair cosmetic score in 11.6% of 3DCRT photon boost patients at the end of 4 years follow-up. Thus, indicating the fact that breast cosmesis improves with time, post-radiation, and better appreciated in long-term follow up studies.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have shown the high likelihood of missing the true peri-lumpectomy target volume when clinical localization focusing on the scar is used [3,4,15]. In our previous planning study [13] we demonstrated that 3D CT based photon boost technique gives better coverage to the tumor bed and higher conformality compared to electron boost and for the superficial targets (tumor bed-skin distance 1 cm to 2 cm) photon boost seems to be the better choice.…”
Section: Discussionmentioning
confidence: 91%
“…However, the limitations of single-field EB plans have been reported by several investigators [8-10]. Kovacs et al [8] reported that EB plans were inferior to XB plans in terms of target coverage and conformity. Toscas et al [9] reported that only superficial tumors could be optimally treated with EB plans.…”
Section: Discussionmentioning
confidence: 99%